Trastorno de estrés postraumático y su afectación en el área emocional de un hombre de 29 años del cantón Las Naves - Acuña Arteaga, Nathaly Karla (2022)
Stress is nothing more than a physical and psychological reaction of the human being inseparable from it, closely related to the emotions of fear and anxiety, the present case study aims to determine the affectation of Post-Traumatic Stress Disorder in the emotional area. of a 29-year-old adult, through the use of psychological techniques, for the improvement of the quality of life of the patient in his mental health, for this the use of the deductive method for the review is carried out as a methodology for the collection of information. bibliography starting from general to specific information content of stress and the emotional area, clinical observation, semi-structured interview and the application of psychometric tests such as: EGS-R, Davidson trauma scale and Zung's depression and anxiety scales , for the collection of information to determine the mental state of the patient, which was recorded in the clinical history with the day presumptive diagnosis F43.1 Post-traumatic stress disorder, with a possible comorbidity in depression disorder, in addition to the results obtained from the patient, it was possible to develop a psychotherapeutic treatment scheme of the cognitive behavioral approach, therefore it can be concluded that it was observed congruence between the theory and the patient's manifestations of discomfort, in addition to the fact that the objective could be met since it was determined that the patient's post-traumatic stress disorder affects the emotional area, through manifestations of sadness, feelings of loneliness, low self-esteem, and maladaptive behaviors such as isolation and irritability.